(untitled) (Bangladesh Journal of Medical Science, 2026)
Background Medical education is characterized by high academic intensity, substantial cognitive and emotional demands, and prolonged exposure to psychosocial stressors. The educational environment has been recognized as a key modifiable determinant influencing student well-being, academic performance, and early professional burnout. However, evidence synthesizing educational environment–related risks within a public health framework remains fragmented. Aim To systematically review and meta-analyze available evidence on risks associated with the educational environment and learning process among medical students, focusing on psychosocial stress, burnout, and perceived quality of the educational environment. Methods A systematic review and meta-analysis were conducted in accordance with PRISMA guidelines. PubMed, Scopus, and Web of Science were searched for studies published between 2009 and 2024. Eligible studies assessed educational environment characteristics (e.g., DREEM), academic stress, burnout, and student well-being. Random-effects metaanalysis was applied to estimate pooled prevalence and associations. Results A total of 1,248 records were identified, of which 42 studies were included in qualitative synthesis and 31 in meta-analysis, encompassing 26,824 medical students from 23 countries. The pooled prevalence of burnout among medical students was 37.23% (95% CI: 32.66–42.05; I² = 98%). High academic stress was reported by approximately 51% of students. Mean DREEM scores ranged from 95.8 to 113.8, indicating predominantly “more positive than negative” perceptions. Metaregression demonstrated that educational environment indicators explained 38.7% of the variance in burnout and stress outcomes. Conclusion: The educational environment of medical universities constitutes a significant psychosocial risk factor affecting student well-being. Risk-oriented assessment of educational settings should be integrated into public health strategies for medical education to support sustainable workforce development. BJMS, Vol. 25 No. 02 April’26 Page: 639-647